Analisis Kinerja Keuangan Pemerintah Daerah Kota Depok - Susiana Setianingsih; Marisa Permatasari; Gede Wijaya Kusuma; Ratna Indriasari (Journal of Innovative and Creativity, 2025)
This study aims to analyze the financial performance of the local government of Depok City for the fiscal years 2019 to 2023 using four financial ratios: fiscal decentralization, financial independence, financial effectiveness, and financial efficiency. A qualitative approach was applied, with data sourced from the budget realization reports of Depok City during the study period. The findings indicate that Depok City’s financial performance is generally strong across all four indicators. The fiscal decentralization ratio reflects the city's growing capacity to generate its own revenue. The financial independence ratio places Depok at a medium-to-high level of autonomy, with an increasingly consultative relationship with the central government—signifying positive progress toward regional self-reliance. The financial effectiveness ratio is very good, as locally generated revenue consistently exceeded set targets, suggesting both accurate budgeting and effective execution. Lastly, the financial efficiency ratio shows that the city's spending was cost-effective and well-managed, with development goals largely achieved within budgetary constraints. These results suggest that Depok City is on the right track in managing its local finances and progressing toward good governance through improved financial accountability and performance.